REVOLUTIONIZING CARDIOVASCULAR CRITICAL CARE: THE PROMISE OF PERSONALIZED THERAPIES BASED ON GENETIC PROFILING - Oliveira, Paula Luzia Seixas Pereira de; Viduedo, Pedro Henrique Zeraik; Martins, Victor Balceiro Legname; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Cardiovascular diseases (CVDs) remain a leading cause of morbidity and mortality worldwide, necessitating innovative approaches to improve patient outcomes in critical care settings. The emergence of genomic medicine has opened new avenues for personalized therapies tailored to an individual's genetic profile. This narrative review not only explores the transformative potential of genetics-based customized medicine in cardiovascular critical care but also instills a sense of optimism about the future. We discuss the impact of genetic variations on disease development, prognosis, and therapeutic responses, highlighting the significance of gene profiling in risk stratification and treatment optimization. Furthermore, we delve into the evolving landscape of pharmacogenomics and its implications for individualized drug therapy in the intensive care unit. By embracing cutting-edge technologies such as gene editing and stem cell therapy, we envision a future where personalized medicine becomes the standard of care in cardiovascular critical care, ultimately improving patient outcomes and reducing the burden of CVDs.